An exploration of how professional graphic design discourse impacts on innovation : a focus on the articulation of a South African design language in i-jusi - Moys, Jeanne Louise (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2004)
This study examines the graphic design industry's call for 'a South African design language' in post-apartheid South Africa and how the non-commercial publication i-jusi is envisaged as a space for graphic designers to innovate a South African design language. The central premise of this research is that graphic design, as a form of cultural production, is discursive. In this respect, graphic design practice is constructed and constrained by professional discourse, which is in turn informed by social structures. However, discourse is also a site of contestation and graphic designers may challenge or negotiate professional discourse in their practice. Thus, as Wolff (1981) argues, the possibility for innovation within graphic design practice may exist at a particular historical moment, although this possibility is itself situated within social structures. In this study, the impact of professional graphic design discourse on the attempt to innovate a South African design language in i-jusi is explored. Utilising qualitative interviews and other texts selected from graphic design commentary (conference presentations and published articles), the motivations of the producers of i-jusi are examined with a view to assessing how their articulation of a South African design language is informed by professional graphic design discourse.
Keywords: Graphic arts -- South Africa; Words in art; Writing in art